Prevalence of bacterial contamination in general operating theaters in selected hospitals in the Gaza Strip, Palestine - Nahed A. Al Laham (Elsevier, 2012)
Summary: Objectives: This study was conducted in general operating theaters at public and private hospitals in the Gaza Strip, Palestine to determine the prevalence of bacterial contamination of different objects. Methods: Swabs were collected from 21 items that were distributed over three categories (equipment, environment and personnel). In total, 243 swabs were collected at pre- and post-operation stages and were cultured and identified using standard microbiological procedures. Results: The results show that 24.7% of the swabs were contaminated with microorganisms. The equipment, environment and personnel were responsible for 45%, 48.3% and 6.7% of contamination, respectively. The rate (26.9%) of contamination in the post-operation samples was higher than in the pre-operation samples (22.6%), but the difference was not statistically significant. In addition, there was not a statistically significant increase in the prevalence of contamination in private (28.7%) compared to public hospitals (21.8%). Of the seven bacterial genera that were recovered, the highest percentage belonged to Staphylococcus spp. (45.3%) followed by Enterobacter spp. (23.4%). Conclusions: This study reveals a moderate percentage of contamination in our public and private hospital general operating theaters, which may increase the risk factors for developing surgical-site infections. These observations justify more attention being paid to infection-control efforts in our hospitals. Keywords: Bacterial contamination, Operating theaters, Gaza Strip, Palestine